THE MODEL ANALYSIS OF REINFORCED BAMBOO WOVEN FOR SHALLOW FOUNDATION SUPPORTING BEARING CAPACITY ON SOFT SOIL - Farhan Heryo Nugroho; Muhammad Zaki (Jurusan Arsitektur - FTSP - Universitas Trisakti, 2022)
North Jakarta generally has soft soil characteristics. Construction built on soft soil is a big problem due to the low bearing capacity of the soil and the large settlement. Therefore, a reinforcement is needed with the aim of increasing the carrying capacity of the soil. In this study using woven bamboo reinforcement, the use of this reinforcement can be an alternative to increase the bearing capacity of the soil used as the basis for shallow foundations. Variations in depth and number of layers of reinforcement are used to obtain the maximum value of the soil bearing capacity. The depth variation used is 0.25B and 0.5B with a variation of 2 (two) layers of reinforcement. The research method used is on a laboratory scale. The data obtained were then analyzed by comparing the value of the bearing capacity of the soil without reinforcement using reinforcement which was expressed by Bearing Capacity Ratio (BCR). The results showed that the largest bearing capacity value occurred in the modeling distance of 0.25B with 2 layers of reinforcement of 459.064 kN/m2 while the smallest value of bearing capacity occurred in modeling of the distance of 0.5B with 1 layer of reinforcement of 321.227 kN/m2 and increased carrying capacity land with an increase value of 76.31 %.